2021
DOI: 10.1002/ange.202100456
|View full text |Cite
|
Sign up to set email alerts
|

Amine‐Tagged Fragmented Ligand Installation for Covalent Modification of MOF‐74

Abstract: MOF‐74 is one of the most explored metal–organic frameworks (MOFs), but its functionalization is limited to the dative post‐synthetic modification (PSM) of the monodentate solvent site. Owing to the nature of the organic ligand and framework structure of MOF‐74, the covalent PSM of MOF‐74 is very demanding. Herein, we report, for the first time, the covalent PSM of amine‐tagged defective Ni‐MOF‐74, which is prepared by de novo solvothermal synthesis by using aminosalicylic acid as a functionalized fragmented o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Many researches have tried to improve both the CO 2 adsorption capacity and selectivity of MOFs, for instance, ligand functionalization [38,39], incorporation of open metal sites [29,40,41], construction of specific pores [17], and pre-/postmodification for amine grafting/impregnation [36,[42][43][44][45][46][47][48]. Zhu et al [42] reported that the polyethyleneimine-modified UiO-66-NH 2 (Zr) exhibited a considerable enhancement toward CO 2 /N 2 adsorption selectivity (48 vs. 25) and moderate desorption energy (68 kJ/mol CO 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many researches have tried to improve both the CO 2 adsorption capacity and selectivity of MOFs, for instance, ligand functionalization [38,39], incorporation of open metal sites [29,40,41], construction of specific pores [17], and pre-/postmodification for amine grafting/impregnation [36,[42][43][44][45][46][47][48]. Zhu et al [42] reported that the polyethyleneimine-modified UiO-66-NH 2 (Zr) exhibited a considerable enhancement toward CO 2 /N 2 adsorption selectivity (48 vs. 25) and moderate desorption energy (68 kJ/mol CO 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, the covalent modification of a defect-engineered Ni-MOF-74 was achieved through the incorporation of an amine-tagged fragment. [54] The installation of the fragment into the framework resulted in defective but highly stable porous MOFs. The amino functionalities of the defective highly stable MOF (DEMOF) were covalently modified with an aldehyde functional group followed by postsynthetic metalation with a Pd complex is shown in Figure 9.…”
Section: Post-synthetic Modification (Psm)mentioning
confidence: 99%
“…Ni-MOF-74 features a one dimensional (1D) hexagonal channel with a size of 11 Å, which is assembled from Ni 2+ with 2,5-dihydroxyterephthalic acid (H 4 DOBDC). This material has high stability in various solvents and strong hydrophilicity, 35 signifying its great potential for pervaporation dehydration. To date, some literature studies have been reported on the preparation Ni-MOF-74 membranes for gas separation.…”
Section: Introductionmentioning
confidence: 99%